The Effect of Tax Aggressiveness on Switching Auditors with Auditor Reputation as a Moderating Variable - Febrian Rizkika Kurnianto; I Gede Wied Jagadhita; Ngurah Ade Satria Laksamana Ananta Prayoga; Partiwi Dwi Astuti (Sekolah Tingg Ilmu Ekonomi Y.A.I Jakarta - Indonesia, 2026)
Auditors need to evaluate business risks before accepting or continuing an audit engagement, including risks that may damage a public accounting firm’s reputation. Companies with high tax aggressiveness may increase reputational risk for auditors and potentially influence auditor switching decisions. However, empirical evidence on the moderating role of auditor reputation remains limited and inconsistent. This study examines the effect of tax aggressiveness on auditor switching, with auditor reputation as a moderating variable. Its novelty lies in testing whether auditor reputation explains inconsistent findings in prior studies. The population comprised companies listed on the Indonesia Stock Exchange during 2020-2022. Using purposive sampling, the study selected 60 companies, yielding 180 firm-year observations. Data were analyzed using logistic regression with a moderated regression analysis approach. The results indicate that tax aggressiveness has a positive but insignificant effect on auditor switching. Furthermore, auditor reputation does not moderate the relationship between tax aggressiveness and auditor switching. This study contributes empirically by demonstrating that auditor switching decisions are not determined solely by tax aggressiveness or auditor reputation, thereby enriching the auditor switching literature and extending understanding of agency theory in the context of developing countries while providing relevant evidence for regulators, auditors, investors, and researchers. Abstrak - Auditor perlu mengevaluasi risiko bisnis sebelum menerima atau melanjutkan perikatan audit, termasuk risiko yang dapat merusak reputasi kantor akuntan publik. Perusahaan dengan agresifitas pajak yang tinggi dapat meningkatkan risiko reputasi auditor dan berpotensi mempengaruhi keputusan auditor switching. Namun, bukti empiris tentang peran moderasi reputasi auditor tetap terbatas dan tidak konsisten. Penelitian ini mengkaji pengaruh agresifitas pajak terhadap auditor switching, dengan reputasi auditor sebagai variabel moderator. Kebaruannya terletak pada pengujian apakah reputasi auditor menjelaskan temuan yang tidak konsisten dalam penelitian sebelumnya. Populasinya terdiri dari perusahaan yang terdaftar di Bursa Efek Indonesia selama 2020-2022. Dengan menggunakan purposive sampling, penelitian ini memilih 60 perusahaan, menghasilkan 180 pengamatan. Data dianalisis menggunakan regresi logistik dengan pendekatan analisis regresi moderat. Hasil penelitian menunjukan bahwa agresifitas pajak memiliki pengaruh positif namun tidak signifikan terhadap auditor switching. Selain itu, reputasi auditor tidak memoderasi hubungan antara agresifitas pajak dan auditor switching. Penelitian ini berkontribusi secara empiris dengan menunjukan bahwa keputusan peralihan auditor tidak hanya ditentukan oleh agresifitas pajak atau reputasi auditor, sehingga memperkaya literatur auditor switching dan memperluas pemahaman tentang teori keagenan dalam konteks negara berkembang dan memberikan bukti yang relevan bagi regulator, auditor, investor, serta peneliti.